2018
DOI: 10.3389/fmolb.2018.00040
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity of Cysteine Proteases Beyond the S2 Pocket: Mutagenesis and Molecular Dynamics Investigation of Fasciola hepatica Cathepsins L

Abstract: Cysteine proteases are widespread in all life kingdoms, being central to diverse physiological processes based on a broad range of substrate specificity. Paralogous Fasciola hepatica cathepsin L proteases are essential to parasite invasion, tissue migration and reproduction. In spite of similarities in their overall sequence and structure, these enzymes often exhibit different substrate specificity. These preferences are principally determined by the amino acid composition of the active site's S2 subsite (pock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…These results are consistent with our previous observations when screening chalcones for cathepsin L inhibition where we found that Fh CL1 activity was easier to disturb and was inhibited by a higher number of the compounds assayed when compared to Fh CL3 [16]. This could be a consequence of the broader conformation of Fh CL1 active site cleft that might accommodate different small molecules straightforwardly [33,34].…”
Section: Resultssupporting
confidence: 92%
“…These results are consistent with our previous observations when screening chalcones for cathepsin L inhibition where we found that Fh CL1 activity was easier to disturb and was inhibited by a higher number of the compounds assayed when compared to Fh CL3 [16]. This could be a consequence of the broader conformation of Fh CL1 active site cleft that might accommodate different small molecules straightforwardly [33,34].…”
Section: Resultssupporting
confidence: 92%
“…Val is present in FhCL1 at this position, the presence of Leu is characteristic of FhCL2. However, a recent study demonstrates that a single change in this position generated by site directed mutagenesis does not affect the specificity of the enzyme (Corvo et al, 2018). These observations reinforce the idea that a diversity of FhCL1 isoforms with subtle differences might be produced simultaneously by the parasite.…”
Section: Resultsmentioning
confidence: 68%
“…The main viral protease, 3CLpro, is a cysteine protease with LQ/(S, A, G) as the preferred P2–P1–P1’ substrate sequence ( Fan, Ma et al 2005 ). In comparison, the optimum substrate recognition motif for rhinovirus 3C protease is ETLGQ/GP ( Cordingley, Callahan et al 1990 ), highlighting the broad range in substrate recognition among cysteine proteases ( Corvo, Ferraro et al 2018 ). Due to its key role in viral replication, 3CLpro is considered a major target for antiviral drug discovery.…”
Section: Introductionmentioning
confidence: 99%